Membangun Generasi Berintegritas melalui Pendidikan Karakter dalam Kurikulum Nasional - Cut Kumala Sari; Tria Nur Maulida; Yeliani Marlina Situmorang (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This article examines the implementation of characterieducationiin Indonesia's national curriculum asian effortito build a generation with high integrity. This literature-based research analyzes various character education models that have been implemented in the national curriculum and identifies challenges and opportunities in their implementation. The results show that character education holistically integrated into the curriculum hasia significantiimpaction developing attitudesiandibehaviors of integrity among students. Supporting factors for successful character education include teacher modeling, conducive schoolenvironments, family support, and community collaboration. The main challenges lie in the consistency of implementation, educator capacity, and evaluation of character value achievements. This article recommends strengthening project-based and experiential learning approaches, developing educator capacity, and comprehensive evaluation models to optimize the process of character formation with integrity in students.